Control of White Rust Disease (Puccinia Horiana Henn.) in Chrysanthemum Plants using a Greenhouse Control System Based on Ardunio Uno - Nababan, Bonitha Elisabet; Kolibu, Hesky Stevy; Mosey, Handy Indra Regain (Universitas Sam Ratulangi, 2024)
Research has been conducted to produce an Arduino Uno-based control system in improving the quality of chrysanthemum production. Data on the state of the greenhouse environment are taken from the DHT22 sensor (air temperature and humidity meter), and BH1750 sensor (light intensity meter). To determine the ability of the control system as a means of controlling white rust disease in chrysanthemums, a comparison of the percentage of white rust disease in greenhouses measuring (5 × 10) m each applied by the control system and without a control system. The results of this study show the response of the control system can work well in the two phases of chrysanthemum growth. The created system is able to automate regular watering of plants and the addition of light according to the needs of chrysanthemums. White rust disease control using a control system was able to produce 14.94% better quality of chrysanthemum crop production than without using a control system. With this control system, it has an impact on the cost of maintaining chrysanthemums such as the use of pesticides in dealing with white rust disease. Keywords: Chrysanthemum Plant, Control System, Greenhouse, White Rust Disease.